NF‐κB‐repressing factor phosphorylation regulates transcription elongation via its interactions with 5'→3' exoribonuclease 2 and negative elongation factor. Issue 1 (4th September 2015) - Rother, Sascha; Bartels, Myriam; Schweda, Aike Torben; Resch, Klaus; Pallua, Norbert; Nourbakhsh, Mahtab
ABSTRACT: NF‐κB‐repressing factor (NKRF) inhibits transcription elongation by binding to specific sequences in target promoters. Stimuli such as IL‐1 have been shown to overcome this inhibitory action and enable the resumption of transcription elongation machinery by an unknown mechanism. Using mass spectrometry and in vitro phosphorylation analyses, we demonstrate that NKRF is phosphorylated within 3 different domains in unstimulated HeLa cells. Phosphoamino acid mapping and mutation analysis of NKRF further suggest that only Ser phosphorylation within aa 421‐429 is regulated by IL‐1 stimulation. In copurification studies, aa 421‐429 is required for interactions between NKRF, 5'→3' exoribonuclease 2 (XRN2) and the negative elongation factor (NELF)‐E in HeLa cells. Chromatin immunoprecipitation experiments further show that IL‐1 stimulation leads to decrease in NKRF aa 421‐429 phosphorylation and dissociation of NELF‐E and XRN2 by concomitant resumption of transcription elongation of a synthetic reporter or the endogenous NKRF target gene, IL‐8. Together, NKRF phosphorylation modulates promoter‐proximal transcription elongation of NF‐κB/NKRF‐regulated genes via direct interactions with elongation complex in response to specific stimuli.—Rother, S., Bartels, M., Schweda, A. T., Resch, K., Pallua, N., Nourbakhsh, M. NF‐κB‐repressing factor phosphorylation regulates transcription elongation via its interactions with 5'→3' exoribonuclease 2 and negative elongation factor. FASEB J. 30, 174‐185 (2016). www.fasebj.org